ENGAGEMENT SYSTEM IN SYLLABUS OF SAME-SEX MARRIAGE LEGAL DOCUMENT OF THE UNITED STATES: A SYSTEMIC FUNCTIONAL LINGUISTICS - Ulfah, Ayu Pratiwi; Sujatna, Eva Tuckyta Sari; Amalia, Rosaria Mita (Study Program of English Literature, 2019)
Supreme Court of the United States ruled that the American Constitution guarantee the same-sex marriage in 2015. It is the syllabus of Same-Sex Marriage in the United States that become the object of the research. This research aims to identify the engagement devices and examines how engagement system in the syllabus of same-sex marriage legal document of the United States that indicates the meaning and relation with the readers. The theory proposed by Martin and White of engagement system (2005) based on appraisal system is used to support the analysis. From the analysis, the researcher found there are 116 heteroglossic and 37 monoglossic types from 153 clauses. The presence of heteroglossic as the most type indicates that the petitioners not only made themselves as references or data sources, but also they tried to add many references and other brackets as data and facts that strengthen their statements. In addition, the presence of 'pronounce' type as the most type in heteroglossic as contract shows that the petitioners made many straightforward and assertive statements. These statements are representative of the assured feeling of the petitioners after seeing the fact that the same-sex marriage was discriminated. The presence of 'entertain' type as the most type in heteroglossic as expand shows us that the petitioners support same-sex marriages so that their rights can be recognized in the United States. Petitioners attest the ideals life of same-sex marriages who will be peaceful and prosperous like the hetero-sex marriages. Because they believe that marriage is fundamental right for all citizen.